ENDOTHELIAL DYSFUNCTION IN ISCHEMIC HEART DISEASE - N. E. Zakirova; R. G. Oganov; A. N. Zakirova; M. P. Plotnikova; G. M. Salakhova (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To assess the role of endothelial vasodilating, vasoconstrictive and adhesive dysfunction in the development of angina pectoris (AP) in patients with ischemic heart disease (IHD).Material and methods. 83 patients with IHD were included in the study. 30 patients had AP of functional class (FC)-II, 27 patients - FC-III and 26 patients - FC-IV. The control group consisted of 25 healthy persons. Bicycle ergometry, daily ECG monitoring and echocardiography were used for verification of IHD. Endothelial vasodilating function was assessed by endothelium-dependent (EDVD) and endothelium-independent vasodilatation (EIDVD) of brachial artery. Vasoconstrictive function was assessed by the level of endothelin (ET-1). Endothelial adhesive function was evaluated by plasma concentration of intracellular adhesion molecules – JCAM-1, VCAM-1 and Е-selectin.Results. Normal EDVD and EIDVD were observed in patients with AP of FC-II. The more severe FC of AP the more prominent endothelial vasodilating dysfunction was revealed as well as the higher levels of ET-1 and intracellular adhesion molecules. Patients with AP of FC-IV had hyperexpression of JCAM-1, VCAM-1, Е-selectin and ET-1 and low levels of EDVD and EIDVD.Conclusion. Progression of IHD related with growing endothelial vasodilating, vasoconstrictive and adhesive dysfunction.